2019
DOI: 10.1523/jneurosci.1164-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Noradrenergic Neuromodulation of Behavior: Impacts of a Modular Locus Coeruleus Architecture

Abstract: The locus coeruleus (LC) is a seemingly singular and compact neuromodulatory nucleus that is a prominent component of disparate theories of brain function due to its broad noradrenergic projections throughout the CNS. As a diffuse neuromodulatory system, noradrenaline affects learning and decision making, control of sleep and wakefulness, sensory salience including pain, and the physiology of correlated forebrain activity (ensembles and networks) and brain hemodynamic responses. However, our understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 134 publications
3
132
2
1
Order By: Relevance
“…Our optogenetic experiments targeted LC cell bodies, and future studies are needed to determine the roles of NE (and dopamine) release at specific projection targets. While LC has been typically regarded as a relatively homogeneous nucleus, some recent studies challenge this view and suggest that LC subpopulations have distinct projections that serve different functions (31). Downstream effects of LC on SEAs could be mediated through direct cortical projections, where -adrenergic receptors mediate cortical desynchronization (32).…”
Section: Mechanisms Controlling Sensory-evoked Awakeningmentioning
confidence: 99%
“…Our optogenetic experiments targeted LC cell bodies, and future studies are needed to determine the roles of NE (and dopamine) release at specific projection targets. While LC has been typically regarded as a relatively homogeneous nucleus, some recent studies challenge this view and suggest that LC subpopulations have distinct projections that serve different functions (31). Downstream effects of LC on SEAs could be mediated through direct cortical projections, where -adrenergic receptors mediate cortical desynchronization (32).…”
Section: Mechanisms Controlling Sensory-evoked Awakeningmentioning
confidence: 99%
“…The present experiments reveal aversive valence at 25-Hz, but not 10-Hz tonic activation, in rats, and, for the first time, questions for future investigations. The physiological mechanisms illuminated in these experiments will need to be integrated with the recent structural evidence of greater specificity of LC subpopulation targeting than previously suspected (23,25). The interaction of these more selective physiological and structural features of LC modulation of brain networks promises a broad array of insights to come with novel functional implications for both basic and clinical brain science.…”
Section: Discussionmentioning
confidence: 99%
“…The brains were extracted and kept in 4% paraformaldehyde. Brains were then sectioned in a vibratome (Leica VT 1000P; Leica Biosystems, Ontario, Canada) in 50 µm 23 thick coronal slices and saved in polyvinylpyrrolidone solution. For immunohistochemistry with Npas4 and DBH, slices were washed in PBS, and then incubated with primary antibodies.…”
Section: Immunohistochemistry and Histologymentioning
confidence: 99%
“…Taken together, these results suggest that pupil signal may be related to a functionalspecific portion of LC in humans. This possibility is worth exploring in future studies since functional specialization within LC has been suggested by recent animal studies (for a review see Chandler et al 2019).…”
Section: Lc Pupil Maskmentioning
confidence: 97%